SYEKH MUHAMMAD SA’ID DAN PERKEMBANGAN TAREKAT NAQSABANDIYAH DI BONJOL (1918-1979 M) - Welda Wilis (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aims to reconstruct the biography of Shaykh Muhammad Saʿid and to analyze his roles and contributions to the development of the Naqshbandiyah Order in Bonjol in the fields of education, religion, and socio-political life. The study employs the historical method with a qualitative approach, encompassing the stages of heuristics (data collection through classical manuscripts, archives, and interviews), source criticism (evaluation of the authenticity and credibility of data), interpretation (contextual analysis of historical events), and historiography (the construction of scholarly narratives). The findings indicate that Shaykh Muhammad Saʿid was a multidimensional figure who played a significant role in the development of the Naqshbandiyah Order as a scholar, educator, and political actor. His contributions are reflected in at least sixteen written works addressing the teachings of the Naqshbandiyah Order, Islamic jurisprudence (fiqh), and theology (tawḥīd). In addition, he established educational institutions such as Surau Air Angek and the Shaykh Muhammad Saʿid Mosque in Bonjol. His involvement in the PERTI organization further reflects his efforts to bridge Islamic spirituality with socio-political movements in the post-colonial era. Thus, this research makes an important contribution to enriching Islamic historiography in West Sumatra and affirms the position of Sufi orders as forces that are not only cultural in nature but also political.